2020
DOI: 10.1016/j.heliyon.2019.e03136
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal effects on physicochemical, sensory attributes, vitamin C, and antioxidant activity of frozen immature Dolichos lablab

Abstract: A B S T R A C TImmature Dolichos bean is popular in the Asian region, which is a potent source of vitamin C, antioxidants as well as other macro and micronutrients. Extending shelf life with retaining maximum quality parameters through hydrothermal treatments (HTT) followed by freezing of immature Dolichos bean were carried out. In particular, samples were undergone HTT (n ¼ 9), cooled at room temperature, packed in HDPE packs and stored in a freezer (-18 CAE2), whereas samples without HTT considered as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Polyphenol content and DPPH of gurum seed oil were found to increase from 22.6 to 25.3 mg GAE / kg oil and 59.2% to 64.7% after pretreatment, respectively [12]. The results of the present study are in line with similar reported studies [17,34,35]. However, by comparing both fresh leaves with pretreated and dried leaves, it is observed that all the mean values of TPC at different pretreatments and drying temperatures had statistical significant difference ( < 0.05) for dried Justicia insularis leaves when compared with the fresh leaves.…”
Section: Antioxidant Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…Polyphenol content and DPPH of gurum seed oil were found to increase from 22.6 to 25.3 mg GAE / kg oil and 59.2% to 64.7% after pretreatment, respectively [12]. The results of the present study are in line with similar reported studies [17,34,35]. However, by comparing both fresh leaves with pretreated and dried leaves, it is observed that all the mean values of TPC at different pretreatments and drying temperatures had statistical significant difference ( < 0.05) for dried Justicia insularis leaves when compared with the fresh leaves.…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…However, this present study shows that every plant is unique. Report [17] has that blanching time and drying temperature could either reduce or enhance antioxidant activity in dried vegetables depending on the vegetable. The highest increase of CUPRAC (492 µmoles Trolox /g) in dried Justicia insularis samples was obtained at BHW60 0 C while the least increase (181 µmoles Trolox /g db) was obtained at BSW 40 0 C. In the same vein, CUPRAC in dried Jatropha tanjorensis leaves at BSW 40 0 C recorded the least increase (269 µmoles Trolox /g db) while the highest increase ( 412 µmoles Trolox /g db) was found at BHW60 0 C. Apart from that, FRAP in both dried vegetables increased as the drying temperature increased from 40 0 C to 60 0 C except at BHW where the content increased to 331 µmole FeSO 4 /g db initially and reduced infinitesimally from 355 to 353 µmoles FeSO 4 /g db in dried Justicia insularis samples.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Being a cheap and rich source of protein, it is known as ‘poor man's protein’. 8 The National Academy of Science (NAS), India classified lablab beans as a potential source of protein. 6 Aside from being a good source of protein, it also offers a lot of complex carbs, minerals, and fibre as well as a low-fat level, which helps to meet SDG 2.…”
Section: Introductionmentioning
confidence: 99%